2017
DOI: 10.1002/ptr.5857
|View full text |Cite
|
Sign up to set email alerts
|

Topical Silymarin Administration for Prevention of Capecitabine‐Induced Hand–Foot Syndrome: A Randomized, Double‐Blinded, Placebo‐Controlled Clinical Trial

Abstract: Hand-foot syndrome (HFS) is a frequent dose-limiting adverse reaction of capecitabine in patient with gastrointestinal cancers. Silymarin is a polyphenolic flavonoid extracted from the Silybum marianum that exhibits strong antioxidant and antiinflammatory activities. In this study, we evaluated silymarin efficacy in prevention of capecitabine-induced HFS in patients with gastrointestinal cancers, as the first human study. During this pilot, randomized, double-blinded, placebo-controlled clinical trial, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
(89 reference statements)
0
42
0
3
Order By: Relevance
“…Of the eligible studies, 12 were RCTs, [9][10][11][12]18,[20][21][22][23][24][25][26] and five were cohort studies. A total of 2081 patients (mean sample size: 122; median sample size with corresponding range: 106 ) were included in this meta-analysis.…”
Section: What's New?mentioning
confidence: 99%
See 3 more Smart Citations
“…Of the eligible studies, 12 were RCTs, [9][10][11][12]18,[20][21][22][23][24][25][26] and five were cohort studies. A total of 2081 patients (mean sample size: 122; median sample size with corresponding range: 106 ) were included in this meta-analysis.…”
Section: What's New?mentioning
confidence: 99%
“…Of the eligible studies, 12 were RCTs, [9][10][11][12]18,[20][21][22][23][24][25][26] and five were cohort studies. [17][18][19]23 The main characteristics of the included studies are shown in Table 1. 11,27 The following prevention strategies were addressed in the analyzed studies: pyridoxine (10 studies) 8,11,12,[19][20][21][22]24,26,27 ; topical urea/ lactic acid (three studies) 8,10,25 ; celecoxib (two studies) 9,28 ; and moisturizing cream, topical silymarin, Fuzheng Jiedusan and neurotropin (four studies).…”
Section: What's New?mentioning
confidence: 99%
See 2 more Smart Citations
“…Plenty of traditional herbal formulas have been employed for HFS. The results of RCTs suggest that herbal medicine can alleviate symptoms, relieve pain, and improve QOL (Elyasi, Shojaee, Allahyari, & Karimi, ; Li et al, ; Zhao et al, ). However, no systematic review to date has analyzed the effects of herbal medicine on chemotherapy‐induced HFS.…”
Section: Introductionmentioning
confidence: 99%